Regulation of Cholesterol Homeostasis by Hedgehog Signaling in Osteoarthritic Cartilage. Issue 1 (January 2016) - Ali, Shabana Amanda; Al‐Jazrawe, Mushriq; Ma, Henry; Whetstone, Heather; Poon, Raymond; Farr, Sarah; Naples, Mark; Adeli, Khosrow; Alman, Benjamin A.
Abstract : Objective: With no effective therapies to attenuate cartilage degeneration in osteoarthritis (OA), the result is pain and disability. Activation of hedgehog (HH) signaling causes changes related to the progression of OA, with higher levels of Gli‐mediated transcriptional activation associated with increased disease severity. To elucidate the mechanism through which this occurs, this study sought to identify genes regulated by HH signaling in human OA chondrocytes. Methods: Using human OA cartilage samples, microarray analyses were performed to detect changes in gene expression when the HH pathway was modulated. Results were analyzed for differentially expressed genes, grouped into functional networks, and validated in independent samples. To investigate the effects of chondrocyte‐specific sterol accumulation, we generated mice lacking Insig1 and Insig2, which are major negative regulators of cholesterol homeostasis, under Col2a1 regulatory elements. Results: HH signaling was found to regulate genes that govern cholesterol homeostasis, and this led to alterations in cholesterol accumulation in chondrocytes. A higher level of Gli‐mediated transcription resulted in accumulation of intracellular cholesterol. In genetically modified mice, chondrocyte‐specific cholesterol accumulation was associated with an OA phenotype. Reducing cholesterol accumulation attenuated the severity of OA in mice in vivo and decreased the expression of proteases in human OA cartilage in vitro. Conclusion: HH signaling regulates cholesterol homeostasis in chondrocytes, and intracellular cholesterol accumulation contributes to the severity of OA. Our findings have therapeutic implications, since reduction of HH signaling reversed cholesterol accumulation and statin treatment attenuated cartilage degeneration.